2007
DOI: 10.1038/sj.hdy.6800941
|View full text |Cite
|
Sign up to set email alerts
|

Dosage effects on heritability and maternal effects in diploid and triploid Chinook salmon (Oncorhynchus tshawytscha)

Abstract: Induced triploidy (3N) in salmon results from a blockage of maternal meiosis II, and hence provides a unique opportunity to study dosage effects on phenotypic variance. Chinook salmon families were bred using a paternal half-sib breeding design (62 females and 31 males) and half of each resulting family was treated to induce triploidy. The paired families were used to test for dosage effects (resulting from triploidy) on (1) the distribution and magnitude of phenotypic variation, (2) narrow-sense heritability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…However, our data generally indicate that triploidy is reducing the efficacy of Chinook salmon's disease resistance. The compromised immune function may result from either a residual effect from the pressureshock and subsequently disrupted development, or, perhaps more likely, increased gene dosage adversely affecting gene expression and epistatic and dominance interactions (Johnson et al, 2007).…”
Section: Transcriptional Differences In Chinook Salmonmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our data generally indicate that triploidy is reducing the efficacy of Chinook salmon's disease resistance. The compromised immune function may result from either a residual effect from the pressureshock and subsequently disrupted development, or, perhaps more likely, increased gene dosage adversely affecting gene expression and epistatic and dominance interactions (Johnson et al, 2007).…”
Section: Transcriptional Differences In Chinook Salmonmentioning
confidence: 99%
“…Triploid Chinook salmon generally exhibit a normal phenotype with few differences from diploid salmon at resting-state (reviewed by Benfey, 1999), although, in seawater trials, survivability of triploid salmonids has generally been lower than that of diploids (O'Flynn et al, 1997;Benfey, 2001;Cotter et al, 2002), suggesting a difference in disease resistance. However, studies on the immunocompetence of triploid salmonids have proven equivocal (reviewed by Bruno and Johnstone, 1990;Yamamoto and Iida, 1995;Benfey, 1999), but the inconsistent results may be because of individual and familial variation or genotype-by-environmental interactions, not ploidy differences (Johnson et al, 2004(Johnson et al, , 2007Miller et al, 2004). Immune challenge studies with a variety of pathogens resulted in either equal competence of triploid and diploid fish, or triploids faring poorly relative to diploids (Bruno and Johnstone, 1990;Dorson et al, 1991;Ojolick et al, 1995;Johnson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In fishes, parental effects are particularly known to have an important role in the development at the embryo and juvenile stages (Green, 2008;Donelson et al, 2009) and have been widely documented in salmonid species (Refstie and Steine, 1978;Fleming, 1999, 2000;Heath et al, 1999;Perry et al, 2004Perry et al, , 2005Johnson et al, 2007;Nichols et al, 2007;Petersson and Järvi, 2007;Wedekind et al, 2008;Eilertsen et al, 2009). These studies have documented the effects of maternal or paternal phenotypic traits (such as color, egg size, weight and length) on the length, fitness, development rate or growth of offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, length and color of the father may be significantly associated with the offspring length (Refstie and Steine, 1978;Perry et al, 2004;Eilersten et al, 2009). In brook charr (Salvelinus fontinalis) and chinook salmon (Oncorhynchus tshawytscha), it has been shown that maternal effects related to growth completely disappear after the yolk sac resorption stage (Heath et al, 1999;Perry et al, 2005;Johnson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Polyploidization also induces direct changes by perturbing cellular architecture, as increasing the DNA content of a cell usually increases its volume (Melaragno et al 1993). The augmentation of genetic material and gene copies obviously has implications that change heterozygosity and lead to additive (Johnson et al 2007) and non-additive (Auger et al 2005) effects on gene expression and resulting phenotypic traits, probably due to disruptions of regulatory pathways and epigenetic instability (Auger et al 2005). By these means, polyploidy has played an important role in plant evolution (Soltis & Soltis 1999, Otto & Whitton 2000, Paterson 2005, though it appears to have occurred more rarely in animal evolution (Orr 1990, but see Mable 2004.…”
Section: Introductionmentioning
confidence: 99%